IDENTIFIKASI PENGARUH PEMASARAN PARIWISATA HALAL DI KOTA LHOKSEUMAWE TERHADAP PEREKONOMIAN MASYARAKAT LOKAL - Samsidar Samsidar; Agustinawati Agustinawati; Dini Aylulliyah; Ayu Safitri (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
The tourism industry in Lhokseumawe City. has experienced rapid development and made Halal tourism a leading sector. This research was conducted   to   determine   promotion of halal tourism   on   the   economics local society in Lhokseumawe City. This study uses a qualitative descriptive  approach. The data were obtained through quisioner and in-depth interviews from Muslim tourism businesses.. The multiple regression method was used to analyze data. The results of the study show that the advertising of halal tourism destinations is very significans influence of economics local society and the quality variables that still need to  be improved are the variables of branding  andselling.